Pengaruh Beban Kerja Terhadap Tingkat Stres Perawat Di Ruang Isolasi Covid-19 Rumah Sakit Aminah Kota Tangerang - Noviana Dwi Mawartiwi; Hendry Kiswanto Mendrofa (Universitas Malahayati, 2022)
ABSTRACT Coronavirus is an infectious respiratory disease, with symptoms such as the common cold-causing symptoms of diseases such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Corona patients or also known as Covid-19 require special handling that is different from ordinary patients. Nurses, especially those in the Covid-19 isolation room, are required to show deep concern. If the demands for tasks are getting higher, it will be a source of stress for nurses. The source of stress for nurses can be in the form of excess workload. Objective To Analyze the Effect of Workload on the Stress Level of Nurses in the Covid-19 Isolation Room at Aminah Hospital, Tangerang City, 2021. Causal-comparative research. The research was conducted in Tangerang Aminah Hospital from March 2021 to April 2021. The population in this study were all nurses in the isolation room Covid 19th Aminah Hospital Tangerang City as many as 45 people to sample as many as 45 people of all nurses in the isolation room Covid-19 Aminah Hospital. The sampling technique was total sampling. The instruments used in the study of time and motion objective workload and questionnaires measuring job stress. Analysis of the data in this study using Spearman Rank Correlation test. Showed the workload of nurses in the Covid-19 Isolation Room at Aminah Hospital, Tangerang City 2021 was the majority being as many as 23 people (51.1%), stress levels of nurses in the Covid-19 Isolation Room, Aminah Hospital, Tangerang City 2021, the majority of moderate stress, as many as 19 people (42.2,%). Based on the analysis of the Spearman Rank test, the p-value is 0.000 <0.05, which means that H0 is rejected. There is an influence between Workload on Nurses' Stress Level in the Covid-19 Isolation Room at Aminah Hospital, Tangerang City 2021 Keywords: Covid-19, Workload, Stress, Nurse ABSTRAK Virus Corona merupakan penyakit infeksi saluran pernapasan, dengan gejala seperti flu biasa menyebabkan hingga bergejala penyakit seperti Middle East Respiratory Syndrome (MERS) dan Sindrom Pernapasan Akut Berat atau Severe Acute Respiratory Syndrome (SARS). Pasien Corona atau disebut juga Covid-19 memerlukan penanganan khusus yang beda dengan pasien biasa. Perawat khususnya di ruang isolasi Covid-19 dituntut untuk menunjukkan kepedulian yang mendalam. Apabila tuntutan akan tugas-tugas semakin tinggi, hal tersebut akan menjadi sumber stres bagi perawat. Sumber stres perawat dapat berupa beban kerja berlebih. Untuk Menganalisis Pengaruh Beban Kerja terhadap Tingkat Stres Perawat Di Ruang Isolasi Covid-19 Rumah Sakit Aminah Kota Tangerang Tahun 2021. Penelitian kausal-komparatif. Penelitian ini dilaksanakan di Rumah Sakit Aminah Tangerang pada bulan Maret 2021 sampai April 2021. Populasi dalam penelitian ini adalah semua perawat di ruang isolasi Covid-19 Rumah Sakit Aminah Kota Tangerang sebanyak 45 orang dengan sampel sebanyak 45 orang semua perawat di ruang isolasi Covid-19 Rumah Sakit Aminah. Teknik pengambilan sampel berupa total sampling. Instrumen yang digunakan dalam penelitian yaitu time and motion pengukuran beban kerja objektif dan kuisioner pengukuran stres kerja. Analisa data dalam penelitian ini menggunakan uji Korelasi Spearman Rank. Hasil menunjukkan beban kerja perawat di Ruang Isolasi Covid-19 Rumah Sakit Aminah Kota Tangerang 2021 adalah mayoritas sedang sebanyak 23 orang (51,1%), tingkat stres perawat di Ruang Isolasi Covid-19 Rumah Sakit Aminah Kota Tangerang 2021, mayoritas stres sedang, sebanyak 19 orang (42,2,%). Berdasarkan analisa uji Sperman Rank diperoleh p value 0,000 < 0,05 yang berarti H0 ditolak. Ada pengaruh antara Beban Kerja Terhadap Tingkat Stres Perawat di Ruang Isolasi Covid-19 Rumah Sakit Aminah Kota Tangerang 2021. Kata Kunci: Covid-19, Beban Kerja, Stres, Perawat